DYNAMICS OF CENTRAL FISCAL TRANSFERS AND THEIR IMPLICATIONS FOR REGIONAL INDEPENDENCE IN JAMBI PROVINCE - Dewi Ernita; Silvia Rahayu; Adek irma Rosi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
The purpose of this study is to examine the extent of fiscal dependence of regional governments on central government transfer funds. By understanding this level of dependence, local governments can formulate strategies to increase local revenue (PAD) and improve the efficiency of regional financial management. Practically, the results of this research are expected to serve as input for the Jambi Provincial Government in formulating more independent and sustainable fiscal policies, optimizing regional revenue potential, and reducing reliance on central government transfers. This study employs a descriptive quantitative method using data from the Regional Budget (APBD) of Jambi Province. The approach is used to illustrate the degree of regional dependence on central government transfers in Jambi Province. The results indicate a high percentage of fiscal dependence, suggesting that the region has not yet optimized its local revenue potential, resulting in continued reliance on central government funds to finance governmental activities.